2019
DOI: 10.1108/maj-08-2018-1986
|View full text |Cite
|
Sign up to set email alerts
|

Team composition and labor allocation in audit teams: a descriptive note

Abstract: The purpose of this descriptive paper is to describe, illustrate, and provide a deeper understanding of team composition and labour allocation in audit teams by quantifying the exact value of resources at different levels of the audit production. Audit teams have been considered as a black box in audit research. Therefore, we report descriptive statistics on (levels and proportions of) hours and costs allocated to auditor ranks (and the number and value, i.e., billing rates, of auditors for different ranks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…The average team has 11.65 years of auditing experience ( TEAM GENERAL EXP ) and consists of 5.7 auditors ( TEAMSIZE ). We report a team size smaller than the average team size of 10 reported in Che and Svanström (2019). Audit teams with higher levels of industry and client‐specific experience also have higher levels of general experience.…”
Section: Analyses and Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…The average team has 11.65 years of auditing experience ( TEAM GENERAL EXP ) and consists of 5.7 auditors ( TEAMSIZE ). We report a team size smaller than the average team size of 10 reported in Che and Svanström (2019). Audit teams with higher levels of industry and client‐specific experience also have higher levels of general experience.…”
Section: Analyses and Resultscontrasting
confidence: 56%
“…The clients in the sample range from large audits (1140.30 hours; $A299,000 fees) to small audits (32.80 hours; $A3,250 fees), with a median of 181.30 hours and $A32,432 fees. In contrast, using a Big 4 Swedish firm sample Che and Svanström (2019) report median audit hours of 301, and Causholli (2016) reports 1407 hours. Panel C of Table 1 includes the descriptive statistics for the categorical control variables.…”
Section: Analyses and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many audit decisions are made by teams. Our findings of the link between moral awareness and professional experience and gender at the individual level may have implications for audit team composition (Che and Svanstrom, 2019), as individual moral awareness most likely impact ethical decisions made by audit teams (Chen et al, 2020). We hope to have provided a stepping stone for future research that wishes to study moral awareness in an audit context.…”
Section: Discussionmentioning
confidence: 75%
“…This dissertation primarily considers auditors who primarily audit small and medium-sized companies, and findings regarding them may not be generalizable to the concept of the auditor in public companies. Auditing small and medium-sized companies differs from auditing public companies in several respects, such as regulations, constraints on the monitoring role of the auditor due to the separation between ownership and control (Collin et al, 2018), and audit team composition (Che & Svanström, 2019), all of which may affect public auditors' views of themselves and their environment. Prior research has also showed that auditors' understandings of the concept of audit quality differ based on whether they audit public or private companies (Brivot et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%